2015
DOI: 10.15395/mkb.v47n1.397
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Ekspresi Vascular Endothelial Growth Factor dan Ekspresi Tissue Factor Berdasarkan Respons Terapi Kemoradiasi Cisplatin pada Penderita Karsinoma Nasofaring Stadium lanjut

Abstract: AbstrakVascular endothelial growth factor (VEGF) merupakan faktor angiogenik yang berperan dalam angiogenesis tumor. Tissue factor (TF) merupakan inisiator utama pembekuan darah dan merangsang protein yang mengatur angiogenesis. Penelitian bertujuan mengetahui perbedaan ekspresi VEGF dengan ekspresi TF pada penderita KNF stadium lanjut berdasarkan respons terapi kemoradiasi. Dilakukan penelitian kohort prospektif pada penderita KNF stadium III, IVa, dan IVb berdasarkan AJCC edisi ke-7 tahun 2010. Ekspresi TF d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…It was explained that in nasopharyngeal carcinoma, the oxygen factor alone is not sufficient to predict radiosensitivity, there are many other biological factors that involve in radiosensitivity (Hendarsih et al 2015). Moreover, the amount of angiogenic factors influence the pathway of radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…It was explained that in nasopharyngeal carcinoma, the oxygen factor alone is not sufficient to predict radiosensitivity, there are many other biological factors that involve in radiosensitivity (Hendarsih et al 2015). Moreover, the amount of angiogenic factors influence the pathway of radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported a significant relationship between the degree of VEGF expression and NPC stage. They also noted that VEGF detection in NPC tissue might be useful for calculating limfe gland metastases and recurrence, assessing clinical stage, and evaluating the prognosis of NPC [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It was explained that in nasopharyngeal carcinoma, the oxygen factor alone is not sufficient to predict radiosensitivity, there are many other biological factors that involve in radiosensitivity. 19 Moreover, the amount of angiogenic factors influence the pathway of radioresistance. Tumor cells with a few angiogenic factors will become radioresistence via hypoxic pathways, whereas tumor cells that have much of angiogenic factors will become radioresistance through intrinsic pathways and ischemic factors.…”
Section: Discussionmentioning
confidence: 99%